Investigating dynamic changes in 3D-printed covalent adaptable polymer networks - Jia, Yixuan; Spiegel, Christoph A.; Diehm, Juliane; Zimmermann, Daniel; Huber, Birgit; Mutlu, Hatice; Franzreb, Matthias; Wilhelm, Manfred; Théato, Patrick; Blasco, Eva; Tsotsalas, Manuel (Macromolecular materials and engineering, 2024)
3D printing technologies have matured to produce complex structures, still they are often limited to static materials. Introducing alkoxyamine bonds into 3D printed structures offers unprecedented possibilities for post-synthetic modification through nitroxide exchange reaction and nitroxide-mediated polymerization. This study provides a comprehensive molecular and macroscopic characterization of 3D-printed alkoxyamine-containing dynamic covalent adaptable networks. The study provides new insights into their dynamic structural and mechanical alterations, making them promising candidates for advanced applications ranging from biomedical engineering to flexible electronics.